Clinical management of pregnant women with Wolff-Parkinson-White Syndrome: diagnosis, treatment and fetal repercussions of interventions (Research, Society and Development, 2022)
Objective: To gather data on the clinical management of pregnant women with Wolff-Parkinson-White Syndrome, including diagnosis, treatment and fetal repercussions of interventions, in order to recognize the best procedures and ensure a good maternal-fetal prognosis. Methodology: Integrative literature review that aims to elucidate the question posed from the PICo strategy "How is the clinical management of pregnant women with Wolff-Parkinson-White Syndrome?", based on articles selected from MEDLINE/PubMed®, BVS MS and WoS. Results: The clinical presentation may be nonspecific and particular, which requires additional tests. Thus, the electrocardiogram is essential for diagnosis and identification of underlying arrhythmias that put mother and fetus at risk. Characteristic accessory pathway findings should be considered, such as the state of ventricular preexcitation: compensatory tachycardia, decreased PR interval, increased QRS complex, delta waves in different leads, and changes in ventricular repolarization. About treatment, except in maternal-fetal hemodynamic risk, it should be postponed to second and third trimesters, being preferable non-invasive therapeutic methods with proven benefits. When drugs are needed, Adenosine, Quinidine, Ibutilide, Propafenone, Verapamil, and Ajmaline have been shown to be safe, Propranolol should be avoided, and Amiodarone and Sotalol are contraindicated. Still, an individualized alternative, for refractory cases, is radiofrequency ablation of the accessory pathway. Conclusion: Wolff-Parkinson-White Syndrome in pregnant women generates great risks and its diagnosis can be a challenge, as well as its treatment, based on antiarrhythmic drugs that are still controversial in pregnancy. The scarcity of current studies on the subject was a limiting factor for the present review.